2017
DOI: 10.1103/physrevb.95.214511
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity with broken time-reversal symmetry in ion-irradiated Ba0.27K0.73

Abstract: Over the last years a lot of theoretical and experimental efforts have been made to find states with broken time reversal symmetry (BTRS) in multi-band superconductors. In particular, it was theoretically proposed that in the Ba1−xKxFe2As2 system either an s + is or an s + id BTRS state may exist at high doping levels in a narrow region of the phase diagram. Here we report the observation of an enhanced zero field muon spin relaxation rate below the superconducting transition temperature for a high quality cry… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
38
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 54 publications
10
38
0
Order By: Relevance
“…Additionally, heat capacity anomalies at the transition to the s+is state have been found to be suppressed at temperatures below T c . These findings are in line with the recent experimental data suggesting the presence of s + is state in overdoped Ba 1−x K x Fe 2 As 2 at x = 0.73 61 , close to the doping where the Lifshitz transition is expected to occur 38,40 . A large broadening of the s + is-region has been found due to the chemical potential renormalization in the superconducting state (BCS-BEC corrections), previously unaccounted for.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Additionally, heat capacity anomalies at the transition to the s+is state have been found to be suppressed at temperatures below T c . These findings are in line with the recent experimental data suggesting the presence of s + is state in overdoped Ba 1−x K x Fe 2 As 2 at x = 0.73 61 , close to the doping where the Lifshitz transition is expected to occur 38,40 . A large broadening of the s + is-region has been found due to the chemical potential renormalization in the superconducting state (BCS-BEC corrections), previously unaccounted for.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, the onset temperatures of the s + is state in Fig.3 are still well separated from T c for most dopings, consistent with the experimental observations of Ref. 61. Note also that the electron bands are incipient in the s + is region; i.e.…”
Section: Fig 3 Phase Diagram As Function Of Temperature (T ) and Dosupporting
confidence: 89%
See 1 more Smart Citation
“…Magnetic susceptibilities for several less hole doped (Ba,K)‐122 systems but exhibiting nevertheless a broad maximum around 120 K similarly as the strongly overdoped K‐122 in contradiction with the expected strongly hole doping dependent freezing temperature T* which separates bad metal behavior at high temperature from the Fermi liquid one at very low ‐temperature for the total multiband system according to the interpetation suggested by Hardy et al . Taken from V. Grinenko et al . …”
Section: Afe2as2 a = K Rb Cs Puzzles –A Challenge For Theorymentioning
confidence: 82%
“…The most of available experimental data are consistent with this picture. So far we have found that only hole overdoped Ba 1−x K x Fe 2 As 2 system that breaks time reversal symmetry in the superconducting state cannot be described by a two-band model [47]. In this case, a three-band model is needed to describe the superconducting properties [48].…”
Section: The Slope Of H C2 At T C Interpreted By a Single-band Modelmentioning
confidence: 99%